Measurement error of mean sac diameter and crown-rump length among pregnant women at Mulago hospital, Uganda - Sam Ali; Rosemary Kusaba Byanyima; Sam Ononge; Jerry Ictho; Jean Nyamwiza; Emmanuel Lako Ernesto Loro; John Mukisa; Angella Musewa; Annet Nalutaaya; Ronald Ssenyonga; Ismael Kawooya; Benjamin Temper; et al. (BMC, 2018)
Abstract Background Ultrasonography is essential in the prenatal diagnosis and care for the pregnant mothers. However, the measurements obtained often contain a small percentage of unavoidable error that may have serious clinical implications if substantial. We therefore evaluated the level of intra and inter-observer error in measuring mean sac diameter (MSD) and crown-rump length (CRL) in women between 6 and 10 weeks' gestation at Mulago hospital. Methods This was a cross-sectional study conducted from January to March 2016. We enrolled 56 women with an intrauterine single viable embryo. The women were scanned using a transvaginal (TVS) technique by two observers who were blinded of each other's measurements. Each observer measured the CRL twice and the MSD once for each woman. Intra-class correlation coefficients (ICCs), 95% limits of agreement (LOA) and technical error of measurement (TEM) were used for analysis. Results Intra-observer ICCs for CRL measurements were 0.995 and 0.993 while inter-observer ICCs were 0.988 for CRL and 0.955 for MSD measurements. Intra-observer 95% LOA for CRL were ± 2.04 mm and ± 1.66 mm. Inter-observer LOA were ± 2.35 mm for CRL and ± 4.87 mm for MSD. The intra-observer relative TEM for CRL were 4.62% and 3.70% whereas inter-observer relative TEM were 5.88% and 5.93% for CRL and MSD respectively. Conclusions Intra- and inter-observer error of CRL and MSD measurements among pregnant women at Mulago hospital were acceptable. This implies that at Mulago hospital, the error in pregnancy dating is within acceptable margins of ±3 days in first trimester, and the CRL and MSD cut offs of ≥7 mm and ≥ 25 mm respectively are fit for diagnosis of miscarriage on TVS. These findings should be extrapolated to the whole country with caution. Sonographers can achieve acceptable and comparable diagnostic accuracy levels of MSD and CLR measurements with proper training and adherence to practice guidelines.